Radiological Markers of the Olfactory Cleft: Relations to Unilateral Orthonasal and Retronasal Olfactory Function - Liu, David T.; Schwarz-Nemec, Ursula; Renner, Bertold; Mueller, Christian A.; Besser, Gerold (Diagnostics, 2020)
The opacification of the olfactory cleft (OC) has been associated with birhinal orthonasal olfaction in patients with chronic rhinosinusitis (CRS). The aim of this study was to determine the associations between monorhinal and birhinal orthonasal, and retronasal olfaction with radiological markers of the OC in a cohort of patients with CRS. Results were analyzed in a CRS-cohort including 13 patients with nasal polyposis (CRSwNP) and 12 patients with non-eosinophilic CRS (non-eCRS). Monorhinal and birhinal orthonasal olfactory function, and OC-air volume were higher in non-eCRS compared CRSwNP. OC-opacification was also higher in CRSwNP compared to non-eCRS. In the entire CRS-cohort, those with higher OC-opacification showed significantly lower orthonasal and retronasal olfactory test results compared to those with lower OC-opacification across all three coronal planes. Similarly, higher unilateral OC-opacification was also associated with lower ipsilateral orthonasal olfactory function. Correlation analysis further revealed a positive correlation between monorhinal and birhinal orthonasal olfaction with ipsilateral and overall OC-air volume. Likewise, birhinal and monorhinal orthonasal, and retronasal olfactory test results correlated negatively with the overall and ipsilateral Lund-Mackay scores. Monorhinal and birhinal orthonasal, and retronasal olfactory function were lower in CRS patients with higher ipsilateral and overall OC-opacification compared to those with lower OC-opacification.
CRIS-Team WoS Importer:2020-12-18